Versatile application of fast green FCF as a visible cholangiogram in adult mice to medium-sized mammals - Tomoyuki Niimi; Nanae Miyazaki; Hironobu Oiki; Mami Uemura; Shihan Zeng; Watcharapon Promsut; Noriaki Ota; Shunji Nonaka; Hajime Takei; Hiroshi Nittono; Seiko Narushima; Ayaka Yanagida; et al. (Scientific Reports)
Abstract An aqueous solution of a common food dye, Fast Green FCF (FG), mimics cholyl-lysyl-fluorescein to visualize embryonic bile flow via single peritoneal injection into intrauterine mouse embryos. Despite its efficacy in embryos, its suitability for adult mice and small to medium-sized mammals remained uncertain. In this study, we investigated FG cholangiography in adult mice, dogs, and goats. The results demonstrate that FG injection enables progressive cholangiography in these species, highlighting its versatility across different animal models without necessitating specialized equipment. To further evaluate diagnostic utility, FG cholangiography was performed in various mouse models of bile flow disorders. FG successfully visualized dilated lumina in the extrahepatic bile duct of BDL mice and revealed aberrant luminal structures in the gallbladder walls of Sox17 +/− or Shh-cre; Sox17flox/− mice. In Mab21l1 −/− mice with contracted gallbladders, FG influx was limited to the gallbladder neck. Moreover, stereomicroscopic video analysis of FG influx into the gallbladder post-fasting revealed differences in gallbladder wall state and its bile composition between Sox17 +/− and wild-type mice, suggesting the potential for detecting variations in gallbladder stored bile properties. These findings underscore the efficacy of FG in facilitating progressive cholangiography across mammalian species.